Notary Liability for Authentic Deed via Video Conference - Tombiling, Marcella Natalia; Thalib, Mutia Cherawaty; Zulfikar Sarson, Mohamad Taufiq (Estudiante Law Journal, 2025)
The creation of authentic deeds through video conferencing has become increasingly popular amidst technological advancements and the need to adapt to social distancing restrictions due to the pandemic. This study aims to identify the challenges and risks faced by notaries in the creation of authentic deeds online and to find solutions for maintaining the validity and integrity of the deeds. The method used is a descriptive qualitative approach with a case study, where data is collected through literature review and interviews with notaries and legal practitioners. The results of the study indicate that the main challenges in the creation of authentic deeds via video conferencing include technical issues, the difficulty of verifying identities without face-to-face interaction, and the risks of fraud or coercion of the parties involved. Proposed solutions include the use of secure identity verification technologies such as electronic signatures and biometrics, as well as the implementation of clearer regulations regarding online authentic deed creation. Additionally, the importance of maintaining process integrity by involving witnesses virtually and ensuring transparency is emphasized. This study concludes that although the creation of authentic deeds through video conferencing presents various challenges, with the proper application of technology and careful oversight, the resulting deeds remain valid and legally binding